2020
DOI: 10.3390/jpm10040245
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Application of Systems Biology in an Understanding of Chronic Rhinosinusitis (CRS) Development

Abstract: Chronic rhinosinusitis (CRS) is an inflammatory disease of the paranasal sinuses. It is defined as the presence of a minimum of two out of four main symptoms such as hyposmia, facial pain, nasal blockage, and discharge, which last for 8–12 weeks. CRS significantly impairs a patient’s quality of life. It needs special treatment mainly focusing on preventing local infection/inflammation with corticosteroid sprays or improving sinus drainage using nasal saline irrigation. When other treatments fail, endoscopic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…In the future, systems biology methods could give us more insight on the cellular level changes in this disease. Already now, the pathways behind CRS and asthma have been investigated with different omics approaches (genomics, transcriptomics, proteomics and metabolomics) [reviewed in (56,57)]. The findings have made biomarker analysis and pointof-care technology development realistic, thus allowing more precise and quicker diagnoses and personalized treatment to be available in the future clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, systems biology methods could give us more insight on the cellular level changes in this disease. Already now, the pathways behind CRS and asthma have been investigated with different omics approaches (genomics, transcriptomics, proteomics and metabolomics) [reviewed in (56,57)]. The findings have made biomarker analysis and pointof-care technology development realistic, thus allowing more precise and quicker diagnoses and personalized treatment to be available in the future clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Modern techniques including genomics (transcriptomics), proteomics, and metabolomics provide comprehensive and un-biased approaches to study biological systems, identify previously unrecognized mechanistic pathways in health and disease, and establish endotypes within a disease. [83][84][85] Systems biology has provided a more holistic understanding of diseases and endotypes. [83][84][85] Proteomic analysis of nasal mucus and mucosa in CRS suggested a trend of increased presence of immunological, metabolic, tissue remodeling, and apoptotic pathways in CRS.…”
Section: Genomics Proteomics and Metabolomicsmentioning
confidence: 99%
“…Proteomic analysis of nasal mucus and mucosa in CRS suggested a trend of increased presence of immunological, metabolic, tissue remodeling, and apoptotic pathways in CRS 86,87 . Metabolomics analysis of low molecular weight compounds (up to 1,500 Da) has been performed in CRS 85 . Fazlollahi et al 88 found that fatty acids (palmitic, oleic, stearic, and lauric) were highly elevated in CRSwNP compared to CRSsNP and control tissues.…”
Section: Toward Developing a Current View Of Crs Molecular Endotypesmentioning
confidence: 99%
“…Modern techniques including genomics (transcriptomics), proteomics and metabolomics provide comprehensive and un-biased approaches to study biological systems, identify previously un-recognized mechanistic pathways in health and disease, and establish endotypes within a disease [81][82][83] . Systems biology has provided a more holistic understanding of diseases and endotypes [81][82][83] . Proteomic analysis of nasal mucus and mucosa in CRS suggested a trend of increased presence of immunological, metabolic, tissue remodeling and apoptotic pathways in CRS 84,85 .…”
Section: Genomics Proteomics and Metabolomicsmentioning
confidence: 99%
“…Proteomic analysis of nasal mucus and mucosa in CRS suggested a trend of increased presence of immunological, metabolic, tissue remodeling and apoptotic pathways in CRS 84,85 . Metabolomics analysis of low molecular weight compounds (up to 1,500 Da) has been performed in CRS 83 . Fazlollahi et al found that fatty acids (palmitic, oleic, stearic, and lauric) were highly elevated in CRSwNP compared to CRSsNP and control tissues 86 .…”
Section: Genomics Proteomics and Metabolomicsmentioning
confidence: 99%